Puerto del AA.HH Bellavista Nanay - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo el puerto del AA.HH Bellavista Nanay con troncos de madera a orillas del rio Nnay.
ENGLISH: The port of AA.HH Bellavista Nanay was observed with wooden logs on the banks of the Nnay River.

SPANISH: Se observo el puerto del AA.HH Bellavista Nanay con troncos de madera a orillas del rio Nnay.
ENGLISH: The port of AA.HH Bellavista Nanay was observed with wooden logs on the banks of the Nnay River.
Port of the AA.HH Bellavista Nanay
Keywords: Iquitos (Perú)|~|Fluvial ports|~|Embarcaderos|~|Perú|~|ports|~|Iquitos (Perú)|~|puertos|~|Perú|~|puerto fluvial y Embarcaderos|~|Perú|~|puertos|~|Iquitos (Perú)|~|ports|~|Peru|~|fluvial port and Embarcaderos|~|Peru|~|ports